Synthesis and Characterization of Ag2MnSnS4, a New Diamond‐like Semiconductor. Issue 24 (2nd August 2018) - Friedrich, Daniel; Greil, Sebastian; Block, Theresa; Heletta, Lukas; Pöttgen, Rainer; Pfitzner, Arno
Abstract : Phase pure Ag2 MnSnS4 was synthesized from the elements using standard high‐temperature solid‐state methods. Its crystal structure was solved from single‐crystal X‐ray diffraction data collected from a pseudo‐merohedrally twinned crystal as well as by Rietveld refinement of X‐ray powder diffraction data. Ag2 MnSnS4 crystallizes in the monoclinic space group Pc (no. 7) with the unit cell parameters a = 6.651(1), b = 6.943(1), c = 10.536(2) Å, β = 129.15(1)°, V = 337.3(1) Å 3, and Z = 2. The tetrahedraly compound crystallizes in a superstructure of the wurtzite type and the tetrahedra volumes are in good agreement with the model for diamond‐related compounds derived from the wurtzite structure type. The red semiconductor Ag2 MnSnS4 has an optical bandgap of Eg = 2.0 eV and is stable up to its peritectic decomposition temperature of approximately 700 °C. Ag2 MnSnS4 is a Curie–Weiss paramagnet with an experimental magnetic moment of μ exp = 5.4(1) μB per manganese atom. Antiferromagnetic ordering is detected at a Néel temperature of T N = 8.8(1) K. 119 Sn Mößbauer spectra at 78 K underline the single tetrahedrally coordinated Sn IV site ( δ = 1.34(1) mm· s –1 ). The 6 K spectrum (magnetically ordered state) reveals a small transferred magnetic hyperfine field of 1.02(1) T. Abstract :